The Effect of Frailty on Balance, Fear of Falling, and Dual-Task Performance in Individuals with Type 2 DM - Meral Sertel; Eylem Tütün Yümin; Merve Bilgin; Hanife Büşra Hekimoğlu; Sinem Özyün; Fatma Nur Körlük (Life)
The aim of this study was to compare balance, fear of falling, and dual-task performance in frail, pre-frail, and non-frail individuals with type 2 DM. The study included 110 voluntary individuals diagnosed with type 2 DM. Individuals with type 2 DM were divided into three groups according to the FRAIL Scale: frail (n = 26), pre-frail (n = 52), and non-frail (n = 32). The FRAIL Scale evaluated individuals’ frailty levels, Timed Up and Go Test evaluated dual-task performance (cognitive and motor), and Tinetti Balance and Gait Scale evaluated balance and risk of falls. Considering the Fall Efficacy Scale, Tinetti Balance and Gait Scale, TUGstandard (sec), TUGcognitive (sec), and TUGmotor (sec) results of frail, pre-frail, and non-frail individuals with type 2 DM, a statistically significant difference was found between the groups (p < 0.05). This difference originated from the frail group. Considering the increase in old age and chronic syndromes, such as DM, it brings about, it was concluded that the early evaluation of older adults for frailty and balance was essential and that individually planned intervention could improve prognosis, reduce falls that might occur due to a loss of balance and muscle strength, and enhance the quality of life in older adults.